2012
DOI: 10.1289/ehp.1104509
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Short-term and Long-term Air Pollution Exposure Associations with Mortality in Two Cohorts in Scotland

Abstract: Background: Air pollution–mortality risk estimates are generally larger at longer-term, compared with short-term, exposure time scales.Objective: We compared associations between short-term exposure to black smoke (BS) and mortality with long-term exposure–mortality associations in cohort participants and with short-term exposure–mortality associations in the general population from which the cohorts were selected.Methods: We assessed short-to-medium–term exposure–mortality associations in the Renfrew–Paisley … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 27 publications
4
45
2
2
Order By: Relevance
“…44 Some other authors proposed that the larger magnitudes of the association between long-term exposure and health may be attributable to cumulative effects that increase the sensitivity of highly exposed population subgroups. 45 However, we also observed similar estimates in the magnitudes of the effects of short-and long-term exposures to PM 2.5 and NO 2 . The reasons for these inconsistent results remain unclear and may be related to differences in study populations, lag patterns, races, regions, exposure assessment methods, the constituents of PM, and the confounders adjustment between studies.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…44 Some other authors proposed that the larger magnitudes of the association between long-term exposure and health may be attributable to cumulative effects that increase the sensitivity of highly exposed population subgroups. 45 However, we also observed similar estimates in the magnitudes of the effects of short-and long-term exposures to PM 2.5 and NO 2 . The reasons for these inconsistent results remain unclear and may be related to differences in study populations, lag patterns, races, regions, exposure assessment methods, the constituents of PM, and the confounders adjustment between studies.…”
supporting
confidence: 78%
“…44,45 For example, in the Renfrew-Paisley cohort study, Beverland et al found that a 10 μg/m 3 increase in average black smoke over 3 days (short-term) was associated with a 1.8% (95% CI: 0.1%-3.4%) increase in all-cause mortality compared with an estimate of a 10% (95% CI: 4%-17%) increase in mortality risk for a 10 μg/m 3 increase in average black smoke from 1970 to 1979 (longterm). 45 This discrepancy might be because of several reasons. Short-term exposure studies capture only part of the total effects of long-term repeated exposure to air pollution.…”
mentioning
confidence: 99%
“…Therefore, higher levels of oxidative stress sustained over long-term exposure could support larger-than-average responses to short-term exposure, in the same way that higher levels of oxidative stress are sustained by asthmatics and people suffering from allergies 33. In addition, long-term exposure directly affects morbidity,34 35 increasing the number of susceptible people and promoting disease progression. Our results add evidence to this discussion by assessing the interaction between short-term and long-term exposures at the individual level over a minimum of 5 years (compared to the 1 year used in most studies).…”
Section: Discussionmentioning
confidence: 99%
“…This supports the hypothesis that long-term exposure actually modifies the effect of short-term exposure on mortality (as has been indicated for smoking40), but it requires the contemporary presence of a pre-existing disease, like COPD, which is known to increase oxidative stress. On the other hand, the higher levels of oxidative stress observed in patients with COPD may be insufficient to induce susceptibility since effect modification was observed only in COPD sufferers living in highly polluted areas, where cumulative exposure34 or the direct effect of long-term exposure41 induces susceptibility in patients with COPD like smoking does. In contrast, the direct effects of long-term exposure on patients with heart disease are more damaging to ischaemic heart disease sufferers (due to greater carotid intima-media thickness and risk of thrombus formation)38 than cardiac arrhythmias sufferers, though there is large evidence that supports that air pollution modifies autonomic tone 42.…”
Section: Discussionmentioning
confidence: 99%
“…Exposuree mortality associations were generally smaller and nonsignificant in the Collaborative cohort, possibly due to the much smaller number and wider geographical distribution of the participants. 22 A more detailed analysis of cause-specific mortality used three different models for estimating long-term exposure to air pollution. 23 Using the most detailed model, exposure to higher levels of air pollution was associated with significantly higher long-term mortality rates due to respiratory and Social position and social mobility across the life-course A series of papers from the Collaborative cohort were among the first to examine the relationship between mortality rates and indicators of socio-economic circumstances at different points in participants' lives.…”
Section: Air Pollutionmentioning
confidence: 99%